Transformation Aeon : Artificial Intelligence Powered Banking - Rucksar Begum, A.; Rajkumar, R.; Amudha, R. (Indian Journal of Computer Science, 2021)
â€œMachine learning is the last invention that humanity will ever need to makeâ€ â€“ Nick Bostrom. Banks are the backbone of financial system. The present technological advancement and the tremendous growth of information technology had bought a drastic transformation in the banking sector. The banking sector in India can be broadly be classified as banking companies, non-banking companies, and the regulatory institutions which regulates them. Though the automation of banking sector is at a nascent stage, the technology is observed to creep into every corner. It has been envisaged that the technological growth of banking helps in improved customer centric services, reduction of fraudulent risks, attainment of financial inclusion, and even more secured operations. Automation has facilitated a direct human involvement. Think about a virtual agent such as Siri, Alexa, Google home which helps us to get solutions instantly. Likewise, AI powered banking may enable a computer system to observe sense, interpret, evaluate, and interact as similar to humans. Thus, this paper tries to analyze the growth rate of Fintech in terms of the application of AI and proliferation of digitalization in banking which could enable relationship banking. Furthermore, the era of financial technology could be a wide opportunity of innovation and automation if AI undergoes a rapid and increased change of reality for financial institutions.